HYDROPONIC EXTENSION OF DRIP IRRIGATION METHOD FOR FRUIT AT PT GREAT GIANT PINEAPPLE - Sismanto, Sismanto; Ali, Fahri; Safitri, Betari; Tiara, Dede; Prajaka, Nanang Wahyu; Hamiranti, Rahmadyah (Politeknik Negeri Lampung, 2023)
PT Great Giant Pineapple (GGP) is the 3rd largest pineapple producer in the world. The cultivationactivities carried out by PT Great Giant Pineapple (PT GGP) still use a conventional system. PT. GGPdoes not yet have facilities and infrastructure that support the development of plant cultivation with ahydroponic system so that cooperation with Politeknik Negeri Lampung (Polinela) is needed in itsdevelopment. The problems faced by PT GGP, especially in the Research & Development section,can be resolved by conducting counseling on hydroponic drip irrigation methods for fruit, especiallymelon plants. By holding hydroponic counseling activities on drip irrigation methods for fruit at PTGreat Giant Pineapple, it is hoped that it can increase the knowledge and understanding of workersand staff at PT GGP on the cultivation and installation of hydroponic drip irrigation methods on melonplants. So that the development of hydroponic melon cultivation techniques with drip irrigationmethods can be carried out independently by partners.